Tendency and Ideology of Arabic and English Online Media - Malihah N.H. Fajrin; Supardi Supardi (Institut Agama Islam Negeri Salatiga, 2021)
This study aims to show the tendencies and ideologies of Arabic and English online media. Al-Jazera and CNN International, as online media, in reporting the death of a journalist named Jamal Kashogi is as a case of the study. This study uses Norman Fairclough’s model of critical discourse analysis which is divided into text analysis, discourse practice, and sociocultural practices. The result of this study suggests that Al-Jazeera and CNN both showed a supportive attitude towards the Kassogi murder case. Aljazeera shows a neutral tendency, while CNN tends to adopt a negative trend towards Westerners because of its ideology. Aljazeera represented the interests and sensibilities of the Middle East with an ideology that appeared to be similar to anti-American view in the presentation of news texts, while CNN could not release the collective consciousness as Westerners.